The Role of Tuo Banda Local Institutions in Improving Competitiveness and Implementation of Salibu Technology in Rice Farming in Tanah Datar District, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2024)
Local Tuo Banda institutions play an important role in irrigation water management to support the application of Salibu technology in rice farming. Data analysis was done quantitatively using the Policy Analysis Matrix (PAM) method. The result showed that Tuo Banda as a local institution in managing irrigation water is very instrumental in ensuring the availability of water for the application of Salibu technology in rice farming in Tanah Datar District, Indonesia. The failure of the implementation of Salibu rice technology so far in some places is due to the absence of local institutions to ensure the availability of irrigation water for Salibu rice farming. Rice business with Salibu technology has competitiveness based on the acquisition of private benefits and social benefits as well as a competitive advantage and comparative advantage.